" The Effect of Gardens Ideas Strategy on Deductive Thinking Among Fourth - Grade Science Students in Physics " (Journal Of Educational and Psychological Researches, 2016)
The current research aims to know the effect of gardens ideas strategy on deductive thinking among fourth-grade science students in physics.    To investigate from the aim of the research, researchers put the following zero hypothesis:- No statistically significant differences at the level of significance (0.05) between the students mean scores of the two groups on indicative thinking test.      The research was carried out on the scientific fourth grade male students in Al – Mansour in Baghdad; belong to Education Directorate Al- Karkh /1, for the Academic Year (2014-2015) A.D.      Prepared research requirements included ] selected the scientific subject chapters ( 5,6,7,8,9  and 10 ) from physics  text book, the formulation of behavioral objectives, prepared  instructional  plans for the experimental groups and control groups[ , after the presentation to a group of specialists .       The researchers applied the research tool by themself, indicative thinking test of (32), according to their psychometric properties.      The research sample was selected intentionally by the researchers which consisted of (80) male students, Randomized into two groups (40) students in experimental group and (40) students in control group.      The two groups students have been equalization by the following variables: (Pre physics knowledge, physics scores at mid-year, age in month, intelligence, indicative thinking).      Experimental group students studied by using indicative thinking strategy and the control group students studied by using traditional method, researcher studied the two research groups by himself three lessons per week.       Research tool was applied, indicative thinking test.      Statistical tools used to deal with the results.      The results showed (There is a statistically significant difference) between the experimental & control group students on indicative thinking test, favor the experimental group students.      According to mentioned  above , the  researchers  had  a number  of  recommendations  which  including  to use gardens ideas strategy  in teaching physics.      In light of the results, Researchers suggested making similar studies in several subjects, and the stages of a study to identify the impact in the achievement, and the attitude towards physics subject and other variables